2012
DOI: 10.3892/ijo.2012.1582
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol exerts an anticancer effect in T98G human glioblastoma cells through the induction of apoptosis and the regulation of adhesion molecules

Abstract: Glioblastoma is one of the most lethal and common malignant human brain tumors, with aggressive proliferation and highly invasive properties. Honokiol derived from Magnolia officinalis is able to cross the blood-brain barrier (BBB) and the blood-cerebrospinal fluid barrier (BCSFB), suggesting a strong possibility that it could be an effective drug for the treatment of brain tumors, including glioblastoma. Thus, we investigated the effects of honokiol on the expression of adhesion molecules in TNF-α-stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
3
24
1
Order By: Relevance
“…In this study, we aimed to investigate the effect of honokiol on the cell invasion process of U87MG human glioblastoma cells through brain microvascular endothelial cells (BMECs) and its possible mechanisms. Thus, first, we examined the cell viability of U87MG cells and BMECs in response to honokiol in a lower range compared to the previous study (22). When U87MG cells and BMECs were treated with indicated honokiol (1-20 µM) for 24 h, the results revealed that honokiol significantly decreased the cell viability of U87MG only at doses of 20 µM (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In this study, we aimed to investigate the effect of honokiol on the cell invasion process of U87MG human glioblastoma cells through brain microvascular endothelial cells (BMECs) and its possible mechanisms. Thus, first, we examined the cell viability of U87MG cells and BMECs in response to honokiol in a lower range compared to the previous study (22). When U87MG cells and BMECs were treated with indicated honokiol (1-20 µM) for 24 h, the results revealed that honokiol significantly decreased the cell viability of U87MG only at doses of 20 µM (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Honokiol is reported to cross the BBB and the BCSFB and to overcome immunoresistance in glioma, strongly suggesting that it could be an effective drug for the treatment of brain tumors, including glioblastoma. Our previous study demonstrated that honokiol induced apoptotic cell death and inhibited cell invasion through regulation of ICAM-1 and VCAM-1 in human glioblastoma T98G cells (22). Recently, it was reported that tumors, including gliomas, contain a small subpopulation of cancer stem cells (CSCs).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many studies have showed that lignans containing typical aromatic rings can cross the BBB [46]. For example, the typical lignan honokiol is able to cross the BBB and the blood-cerebrospinal fluid barrier, and it exerts an anticancer effect [47,48]. Furthermore, six lignans have been detected directly in rat brain tissue after oral administration of lignan extracts [49].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the major lignans with high bioavailability, honokiol exhibits multiple biological properties, including muscle relaxant, neuroprotective, anti-inflammatory and anticancer effects (14)(15)(16)(17)(18)(19). However, whether honokiol exhibits an effect UBC cell migration and invasion remains unclear.…”
Section: Introductionmentioning
confidence: 99%